Migration of Garganey Anas querquedula and Teal Anas crecca in north-eastern Slovenia - Vogrin, Milan (Ornis Svecica, 1999)
Migration patterns and occurrence of Teal Anas crecca and Garganey Anas querquedula were studied in the fishpond complex Racki ribniki (35 ha) in northeastern Slovenia between 1985 and 1996. Peak numbers of Teal in spring occurred in February and in autumn during November. Spring peak numbers of Garganey occurred in April, whereas in autumn the migration was less pronounced. During the spring migration the differences in numbers between months were highly significant. In spring, males were significantly more common than females. Comparisons with other localities in Slovenia showed that the Racki ribniki ponds are important sites for both species during migration.